2020
DOI: 10.1038/s41598-020-69898-9
|View full text |Cite|
|
Sign up to set email alerts
|

Gaze behaviour to lateral face stimuli in infants who do and do not receive an ASD diagnosis

Abstract: Cerebral lateralisation of function is a common characteristic across vertebrate species and is positively associated with fitness of the organism, in humans we hypothesise that it is associated with cognitive fitness. This investigation evaluated the early development of lateralised gaze behaviour for face stimuli in infants at high and low risk for autism from the British Autism Sibling Infant Study (BASIS). The BASIS cohort includes a low risk group and three high-risk groups who at age 3 were developing (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…However, research suggests that reversed brain organization occurs least frequently in the general population (reviewed in Vingerhoets, 2019) and that the frequency of reversed brain organization rises in populations of individuals with autism (e.g., Forrester, Davis, Malatesta, & Todd, 2020). Moreover, studies of infants and children have revealed positive relationships between the direction of behavioral biases and cognitive performance (Donati, Davis, & Forrester, 2020;Forrester et al, 2020;Forrester, Davis, Mareschal, Malatesta, & Todd, 2019).…”
Section: Data Availability Statement: N/amentioning
confidence: 99%
See 2 more Smart Citations
“…However, research suggests that reversed brain organization occurs least frequently in the general population (reviewed in Vingerhoets, 2019) and that the frequency of reversed brain organization rises in populations of individuals with autism (e.g., Forrester, Davis, Malatesta, & Todd, 2020). Moreover, studies of infants and children have revealed positive relationships between the direction of behavioral biases and cognitive performance (Donati, Davis, & Forrester, 2020;Forrester et al, 2020;Forrester, Davis, Mareschal, Malatesta, & Todd, 2019).…”
Section: Data Availability Statement: N/amentioning
confidence: 99%
“…We do not know if this is still true in humans. Therefore, it is necessary that we gain a better understanding of the role that early sensory-motor biases play in supporting the development of higher-order cognitive abilities (Donati et al, 2020;Forrester et al, 2019;Forrester et al, 2020;Forrester & Todd, 2018;Michel, Babik, Nelson, Campbell, & Marcinowski, 2013). Some studies suggest that the strength of bias may be more important for cognitive development than the direction of the bias as an indication of functional specialization (Mellet et al, 2014).…”
Section: Data Availability Statement: N/amentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study demonstrated that early biases in gaze behavior for face stimuli may be considered as behavioral markers of atypical cerebral lateralization patterns. Six-month-old infants, who received an ASD diagnosis at 3 years, were slower to look at faces presented on the left compared to a group of at low-risk (LR) infants 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Both the similarity and differences among species can help us understand the evolution of neurocognitive features and behaviours. Species as close to humans as primates enable scientists to look at brain structures and pathways (e.g., sulcal morphology 1 ; fast visual responses in the amygdala 2 ) and behavioural characteristics thought to be exclusive to our species (e.g., left-cradling bias 3 ; lateral eye bias 4 ; handedness 5 ; abstract concept learning 6 ), and investigate their neuroanatomical, genetic, and environmental basis (e.g., mutual gaze in social communication 7 ). At the same time, the study and comparison of phylogenetically distant species, like birds or fish, can be ideal for testing predictions about the generality and conservation of brain mechanisms across the evolutionary tree (e.g., inhibition of return in barn owls 8 ; Approximate Number System in zebrafish 9 ; numerical discrimination in domestic chicks 10 ; visual mental manipulation in Grey parrot, children, and human adults 11 ).…”
mentioning
confidence: 99%